Voltage sag mitigation using NAS battery-based standby power supply - Hussien Z.F.; Ismail A.B.; Lee W.C.; Busrah A.M.; Siam M.F.M. (2023)
Advances in industrial automation and manufacturing systems led to the utilization of advanced systems comprise of computers, adjustable speed drives and various industrial control systems that are sensitive to power quality problem, mainly voltage sags. Voltage sag is the reduction of the voltage at a user position with duration of between one cycle and a few seconds caused by motor starting, short circuits and fast reclosing of circuit breakers that may cause expensive shutdowns to manufacturers. This paper proposes a Standby Power Supply (SPS) configuration using Sodium Sulfur (NAS) battery for voltage sag mitigation. An electrical battery model is developed for the NAS battery. Simulation results of the electrical battery model are compared and validated experimentally. In addition, voltage sag detection and power conversion system (PCS) model of the system is also described. Using the proposed NAS-SPS configuration system, power quality mitigation is simulated to observe its performance in protecting an important load. The simulation work described in this paper is carried out using EMTDC/PSCAD software tool. The research work was undertaken by TNB Research and Universiti Tenaga Nasional in collaboration with Tokyo Electric Power Company (TEPCO) in a study on the use of NAS battery-based SPS. 2005 IEEE.